THE IMPORTANCE OF MARKETING ACTIVITIES FOR THE FUNCTIONING OF THE UNIVERSITY - Szeląg-Sikora, Anna; Oleksy-Gębczyk, Aneta; Kowalska-Jarnot, Katarzyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
At a time when the number of universities is growing, taking care of the image of a university is increasingly important. Traditional methods of promotion are no longer sufficient, because nowadays the choice of a university starts not with a visit to the university, but with checking its educational offerings on the Internet. This is why, in the digital age, universities need to adapt their marketing strategy to the new realities in order to reach prospective students and stand out from the competition. Many universities are actively taking advantage of the opportunities offered by the development of information technology, appreciating the importance of branding and adapting their course. This paper attempts to identify which 'communication pathway' is most frequently used by prospective university/faculty students. The aim of the study is to determine the effectiveness of promotional activities that influence prospective students' choice of university/department. The issues raised seem to be important due to the fact that radical changes in the education market have been taking place for several years now. On the one hand, there is a large supply of higher education institutions, both domestic and foreign, and on the other hand, there is a progressive demographic decline.